Development and Validation of a Motivation Scale for Status Pursuit by Organization Members - Wang, Zhicheng (Frontiers in Psychology, 2022)
Based on a literature review and questionnaire survey, the study proposes two tendencies of employees’ status pursuit motivation. It applies exploratory factor analysis, confirmatory factor analysis, and other statistical methods to develop a scale of motivation for status which contains nine items and two dimensions. The development stage of this scale consists of the generation of the initial scale, exploratory research and verification research. In the generation stage of the initial scale, we obtained 12 initial questions of the status scale by combing status literature and adopting open questionnaire among employees of knowledge-based enterprises, and determined 10 of them as the questions of the initial scale by text analysis method. In the exploratory research stage, we conducted pre-survey and formal questionnaire collection on some enterprises in Guangdong and Jiangsu provinces of China. In the pre-survey stage, we distributed 100 questionnaires (81 were recovered), and the pre-survey results were satisfactory. Accordingly, 400 questionnaires were distributed (370 were recovered). In the exploratory research stage, we verified the organization member status pursuit motivation scale consisting of two dimensions and nine items. In the stage of validation research, 450 questionnaires were distributed to knowledge-intensive enterprises in Guangdong province, Jiangsu Province, Jiangxi Province and so on (425 were returned). The validation research on organizational membership motivation scale included violation estimation test, confirmatory factor analysis, model fit evaluation, reliability and validity test. Finally, a scale of status pursuit motivation of organization members consisting of two dimensions and nine items is obtained. This study expands the measurement methods of status research from a new perspective and lays a foundation for subsequent empirical research on organizational member status pursuit motivation.